Ecological and sanitary impacts of bacterial communities associated to biological invasions in African commensal rodent communities. Issue 1 (December 2017) - Diagne, Christophe; Galan, Maxime; Tamisier, Lucie; d'Ambrosio, Jonathan; Dalecky, Ambroise; Bâ, Khalilou; Kane, Mamadou; Niang, Youssoupha; Diallo, Mamoudou; Sow, Aliou; Gauthier, Philippe; Tatard, Caroline; et al.
Abstract Changes in host-parasite ecological interactions during biological invasion events may affect both the outcome of invasions and the dynamics of exotic and/or endemic infections. We tested these hypotheses, by investigating ongoing house mouse (Mus musculus domesticus ) and black rat (Rattus rattus ) invasions in Senegal (West Africa). We used a 16S gene rRNA amplicon sequencing approach to study potentially zoonotic bacterial communities in invasive and native rodents sampled along two well-defined independent invasion routes. We found that individual host factors (body mass and sex) were important drivers of these bacterial infections in rodents. We observed that the bacterial communities varied along invasion routes and differed between invasive and native rodents, with native rodents displaying higher overall bacterial diversity than invasive rodents. Differences in prevalence levels for some bacterial Operational Taxonomic Units (OTUs) provided support for ecological processes connecting parasitism and invasion success. Finally, our results indicated that rodent invasions may lead to the introduction of exotic bacterial genera and/or to changes in the prevalence of endemic ones. This study illustrates the difficulty of predicting the relationship between biodiversity and disease risks, and advocate for public health prevention strategies based on global pathogen surveillance followed by accurate characterization of potential zoonotic agents.